2018
DOI: 10.5964/jnc.v3i3.106
|View full text |Cite
|
Sign up to set email alerts
|

A one-year classroom-randomized trial of mental abacus instruction for first- and second-grade students

Abstract: Mental Abacus (MA) is a popular arithmetic technique in which students learn to solve math problems by visualizing a physical abacus structure. Prior studies conducted in Asia have found that MA can lead to exceptional mathematics achievement in highly motivated individuals, and that extensive training over multiple years can also benefit students in standard classroom settings. Here we explored the benefits of shorter-term MA training to typical students in a US school. Specifically, we tested whether MA (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Consistent with this, even children with typical levels of visuospatial ability can readily acquire physical and mental abacus expertise (Barner et al, 2016(Barner et al, , 2018. In particular, by presenting numerically relevant information in regions that even novices automatically attend to, the design of the abacus may scaffold learning how the device represents number, and thus make expertise more easily attainable.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Consistent with this, even children with typical levels of visuospatial ability can readily acquire physical and mental abacus expertise (Barner et al, 2016(Barner et al, , 2018. In particular, by presenting numerically relevant information in regions that even novices automatically attend to, the design of the abacus may scaffold learning how the device represents number, and thus make expertise more easily attainable.…”
Section: Discussionmentioning
confidence: 80%
“…These findings contribute to a rich literature that has indicated that both abacus training and design play a role in explaining abacus expertise (Barner et al, 2016(Barner et al, , 2018Dong et al, 2016;Frank & Barner, 2012;Hu et al, 2011;Wang et al, 2013;Yao et al, 2015). To address this question, we administered a series of visual search tasks to abacus experts and subjects who had little to no experience with the abacus.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations